Photoreduction of gaseous oxidized mercury changes global atmospheric mercury speciation, transport and deposition. Issue 1 (December 2018) - Saiz-Lopez, Alfonso; Sitkiewicz, Sebastian; Roca-Sanjuán, Daniel; Oliva-Enrich, Josep; Dávalos, Juan; Notario, Rafael; Jiskra, Martin; Xu, Yang; Wang, Feiyue; Thackray, Colin; Sunderland, Elsie; Jacob, Daniel; et al.
Abstract Anthropogenic mercury (Hg(0)) emissions oxidize to gaseous Hg(II) compounds, before deposition to Earth surface ecosystems. Atmospheric reduction of Hg(II) competes with deposition, thereby modifying the magnitude and pattern of Hg deposition. Global Hg models have postulated that Hg(II) reduction in the atmosphere occurs through aqueous-phase photoreduction that may take place in clouds. Here we report that experimental rainfall Hg(II) photoreduction rates are much slower than modelled rates. We compute absorption cross sections of Hg(II) compounds and show that fast gas-phase Hg(II) photolysis can dominate atmospheric mercury reduction and lead to a substantial increase in the modelled, global atmospheric Hg lifetime by a factor two. Models with Hg(II) photolysis show enhanced Hg(0) deposition to land, which may prolong recovery of aquatic ecosystems long after Hg emissions are lowered, due to the longer residence time of Hg in soils compared with the ocean. Fast Hg(II) photolysis substantially changes atmospheric Hg dynamics and requires further assessment at regional and local scales. Reduction of gaseous Hg(II) compounds drives atmospheric mercury wet and dry deposition to Earth surface ecosystems. Global Hg models assume this reduction takes place in clouds. Here the authors report a new gas-phase Hg photochemical mechanism that changes atmospheric mercury lifetime and its deposition to the surface.